1987
DOI: 10.1111/j.1399-3054.1987.tb04337.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of polyamines to different parts of various plant species

Abstract: J. 1987. Association of polyamines to different parts of various plant species. -Physiol. Plant. 71: 245-250.The variation in polyattiine content in different plant species and in different parts within a plant can be considerable. To get genera! information about levels of polyamines in plants and about the association of polyattiines to different types of tissue, 30 plants from 13 plant families were examined for their polyamine content before and after gennination using high pressure liquid chromatography (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
3

Year Published

1989
1989
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 15 publications
1
18
0
3
Order By: Relevance
“…The effect of exogenous PAs or their biosynthetic inhibitors has been commonly employed to evaluate the role of PAs in various plant and developmental processes (Egea-Cortines and Mizrahi 1991 ). Felix and Harr (1987) found that the inhibitors neither deplete PA levels nor inhibit germination of seeds of sugar maple (Acer saccharum).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of exogenous PAs or their biosynthetic inhibitors has been commonly employed to evaluate the role of PAs in various plant and developmental processes (Egea-Cortines and Mizrahi 1991 ). Felix and Harr (1987) found that the inhibitors neither deplete PA levels nor inhibit germination of seeds of sugar maple (Acer saccharum).…”
Section: Discussionmentioning
confidence: 99%
“…Ainda segundo esses mesmos autores é possível que, como as giberelinas, as poliaminas possam estar envolvidas tanto na divisão quanto na elongação celular. Felix & Harr (1983) observaram que o conteúdo total de poliaminas é maior em sementes embebidas do que em sementes secas. Isso apoia a hipótese de que o acúmulo de putrescina (a poliamina mais abundante) observado no embrião durante a embebição das sementes é devido à sua síntese líquida e, provavelmente, está relacionado às numerosas divisões celulares que ocorrem no início da germinação.…”
Section: 6 ------------------------------------------------------% Dunclassified
“…Polyamines accumulate in relatively high quantities in resting seeds (Felix and Harr 1987). The polyamines accumulated in embryos of Avena fatua and Oryza sativa, but their content in endosperms was low.…”
Section: Introductionmentioning
confidence: 99%